2020
DOI: 10.1111/jmp.12506
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Toxoplasma gondii in a lethal toxoplasmosis outbreak affecting captive howler monkeys (Alouatta sp.)

Abstract: Background Toxoplasmosis is a zoonotic disease that affects humans and warm‐blooded animals. This study describes an outbreak of toxoplasmosis in howler monkeys (Alouatta sp.) and survival of capuchins (Sapajus apella), under the same environmental conditions. Methods Howler monkeys were submitted to post‐mortem examination. Tissue samples were processed to histopathology and immunohistochemistry to detect lesions and tachyzoites of Toxoplasma gondii. Tissue samples were also frozen and submitted to PCR and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 31 publications
(52 reference statements)
6
23
0
Order By: Relevance
“…There are marked differences in the natural resistance against T. gondii in this group of animals, due to behavioral, ecological, physiological, and evolutionary differences between the species; therefore, mortality rates vary from 0% to 100%, depending on the severity. 2,4,13 When infected with T. gondii, a primate may present neurological clinical signs such as motor incoordination due to encephalitis caused by the installation of protozoan cysts in the central nervous system, 11 which is the same clinical sign reported in the animals in this study.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…There are marked differences in the natural resistance against T. gondii in this group of animals, due to behavioral, ecological, physiological, and evolutionary differences between the species; therefore, mortality rates vary from 0% to 100%, depending on the severity. 2,4,13 When infected with T. gondii, a primate may present neurological clinical signs such as motor incoordination due to encephalitis caused by the installation of protozoan cysts in the central nervous system, 11 which is the same clinical sign reported in the animals in this study.…”
Section: Discussionsupporting
confidence: 68%
“…There are marked differences in the natural resistance against T . gondii in this group of animals, due to behavioral, ecological, physiological, and evolutionary differences between the species; therefore, mortality rates vary from 0% to 100%, depending on the severity 2,4,13 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies on Blastocystis assessed the genetic variability and host specificity, reporting different subtypes (ST1-ST5, ST8) [42,61,116]. Studies on Trypanosoma cruzi identified the genetic lineages of the parasite (TcI-TcIII, TcV, TcVI) [64,90] as well as types of Toxoplasma gondii (Type I, Type II, non-archetypal) [39,100]. Molecular approaches were less frequent in studies of nematodes: Trypanoxyuris sp., Dipetalonema sp., Mansonella sp., Brugia sp., Pterygodermatites sp.…”
Section: Discussionmentioning
confidence: 99%